The Laser Rotating of Non-contact Body Scanning System (Journal of Fiber Bioengineering and Informatics, 2015)
This paper focus on the requiring of Made To Measure apparel production mode according to individual\rtypes and make calibration about body measurement and production in a line. In this paper, based on the\rmeasurement principle of structured light, a laser rotating body scanning of non-contact measurement\rsystem is introduced. Firstly, the key part of this system, such as digital motor, CCD, lens, etc, is\rintroduced and discussed. Secondly, the principle of the whole system is brought up by analyzing\rthe theory and realization of the structured light measurement, and a 3D reconstruction mathematical\rmodel is built based on the characteristic parameter of digital motor. Lastly, some important factors\rrelated to the accuracy of this system are discussed. The point cloud data of 3D body contour is acquired\rsuccessfully via data processing and data piecing together. The further processing can be done according\rto the raw data. The validity of the principle of this system and the feasibility of arithmetic are veri\fed\rby experiments.
Keywords: Laser; Structured Light; Mathematical Model; Non-contact Measurement; Body Scanning